Exponential inequalities for a class of operators - Hans P. Heinig (International Journal of Mathematics and Mathematical Sciences)
Characterizations of weight pairs are proved for which weighted exponential-logarithmic integral inequalities are satisfied. The results given contain characterizations of weights for which inequalities involving the Riemann-Liouville and Laplace type operators hold.